Brood : a novel - Polzin, Jackie, 1979- (Doubleday, 2021)
"Our nameless narrator stubbornly tries to keep her small brood of four chickens alive and safe over the course of one savage winter in Minnesota. Woefully unprepared for the task, she battles the relentless predators, severe weather and unforeseen bad luck--all the while grieving a recent miscarriage, and coming to terms with her infertility and the accompanying uncertainty that her future holds. Intimate and startlingly original, this slender novel is packed with sorrow and joy. Brood is a stunning meditation on longing, grief, and relentless hope"--